Consumer Attitudes And Behaviour Towards Durian Lempuk Products At Giwi Gewi Gift Shop - Oktaviani, Dinda; Hartika, Rika Yuli Dwi; Fariadi, Herri (Utami Publisher, 2025)
Durian (Durio zibethinus) is a tropical plant that produces delicious fruit that is very popular. During the fruiting season, many durians are marketed fresh at varying prices. In general, durian fruit is consumed fresh and only a few are processed into processed products. For farmers, one of the problems they face is the high difference between selling prices at the farmer level and retail selling prices. Apart from that, the technology for processing durian fruit is very limited so farmers are forced to sell it fresh at prices determined by collecting traders. And the aim is to find out consumer attitudes towards soft durian products in the Giwi Gewi souvenir shop, Bengkulu City, and to find out consumer behavior towards soft durian products in the Giwi Gewi souvenir shop, Bengkulu City. Based on the results of research analysis using analysis, several conclusions can be drawn as follows: The average respondent assessment of attitudes is 3.03. The average respondent assessment of behavior is 0.79 with the highest percentage being 100%. The N value or number of respondents is 96, the race value is 25 for attitude and six for behavior, the minimum value is 13 for attitude and four for behavior. , the respective numbers are attitudes 2918 and behavior 767, the mean or mean for each is 30.40 for attitudes and 7.99 for behavior.